New reports on Chinese Anelytra species (Orthoptera, Tettigoniidae: Conocephalinae) - Li, Shan; Zhang, Qianwen; Bian, Xun (Zootaxa, 2023)
Based on the former studies and new material, Anelytra (Euanelytra) eunigrifrons Ingrisch, 1998 is reported in China for the first time. In addition, the female sex of Anelytra (Euanelytra) spinia Shi & Qiu, 2009 is described. We also confirmed that Anelytra (Euanelytra) spinia Shi & Qiu, 2009 is mainly distributed in Southern China. The examined specimens are deposited in Guangxi Normal University.